Comparative efficacy of tulathromycin versus a combination of florfenicoloxytetracycline in the treatment of undifferentiated respiratory disease in large numbers of sheep (Journal of Advanced Veterinary and Animal Research, 2015)
The objective of this study was to compare theefficacy of tulathromycin (TUL) with a combinationof florfenicol (FFC) and long-acting oxytetracycline(LAOTC) in the treatment of naturally occurringundifferentiated respiratory diseases in largenumbers of sheep. In this study, seven naturaloutbreaks of sheep pneumonia in Garmsar, Iran wereconsidered. From these outbreaks, 400 sheepexhibiting the signs of respiratory diseases wereselected, and the sheep were randomly divided intotwo equal groups. The first group was treated with asingle injection of TUL (dosed at 2.5 mg/kg bodyweight), and the second group was treated withconcurrent injections of FFC (dosed at 40 mg/kg bwt)and LAOTC (dosed at 20 mg/kg bwt). In the firstgroup, 186 (93%) sheep were found to be cured 5 daysafter the injection, and 14 (7%) sheep needed furthertreatment, of which 6 (3%) were cured, and 8 (4%)died. In the second group, 172 (86%) sheep were curedafter the injections, but 28 (14%) sheep needed furthertreatment, of which 10 (5%) were cured, and 18 (9%)died. This study revealed that TUL was moreefficacious as compared to the combined treatmentusing FFC and LAOTC. As the first report, this fieldtrial describes the successful treatment ofundifferentiated respiratory diseases in largenumbers of sheep. Thus, TUL can be used for thetreatment of undifferentiated respiratory diseases insheep.http://dx.doi.org/10.5455/javar.2015.b86